Female Dental Student’s Perception of Their Dental Aesthetics and Desired Dental Treatment - Abidia, Randa F.; Azam, Ambreen; El –Hejazi, Ahmed. A.; Al-Mugbel, Khuloud .K.; Haider, Mehdiya. S.; Al-Owaid, Noura. M. (European Scientific Journal, ESJ, 2017)
Objectives: This study aims to assess the self-perception of female dental students of their dental aesthetics regarding their satisfaction, its effect on their quality of life and felt need for treatment. Materials and Method: This is a descriptive study for 1st, 2nd and 3rd year dental students (n=110) in the College of Dentistry at Princess Nourah University (PNU). The survey was distributed via link "Google form". A 20 item questionnaire was prepared and tested before on seven students for clarity. Questions were regarding how students feel about their dental aesthetics and what they desire for treatment. Whether they felt their teeth affected their attractiveness, confidence and quality of life. Data was entered in SPSS for statistical analysis. Results: With a response rate of 94.5% majority (89.4%) of students felt their teeth affected the attractiveness of their faces. Almost one third (30.8%) have tried to hide their smile. Around half (51%) were not satisfied with their tooth colour. Almost two thirds of students (61.5%) felt their quality of life is affected by the appearance of their teeth. ‘Tooth whitening’ was selected by almost two thirds of students (64.4%) followed by almost half (46.2%) the students wanting ‘orthodontic treatment’. Conclusion: Dental aesthetics is rated highly among female dental students.The majority of the students felt that their teeth affected the attractiveness of their face and influenced their quality of life. Students desired teeth whiteneing followed by orthodontic treatment as their perceived need for aesthetic dental treatments.